Serum Cortisol as a Predictor of Major Adverse Pulmonary Event in Emergency Department Acutely Dyspneic Patients - Dikme, Ozlem; Dikme, Ozgur (Emergency Medicine International, 2018)
Cortisol is a steroid hormone released from the adrenal glands in response to stressful conditions. Elevated cortisol levels have been described in stress, but it is unclear whether these are associated with adverse outcomes. In this study, we assess whether cortisol levels drawn in patients presenting with dyspnea to the ED were a predictor of major adverse pulmonary event (MAPE). In 87 patients presenting with dyspnea to the ED, cortisol levels were determined. Patients were then assessed to determine the following MAPE: endotracheal intubation (ETI) in the ED, admission to the intensive care unit (ICU), and in-hospital all-cause mortality. Forty-four patients (50.6%) were female and 33 (37.9%) were diagnosed with heart failure. Cortisol levels in patients with and without MAPE were 34.3μg/dL and 23.8μg/dL, respectively (p<0.001). Also, cortisol levels were found higher in patients intubated in the ED than nonintubated patients (54.2μg/dL vs 25.7μg/dL, p<0.001), higher in patients admitted to the ICU (38.7μg/dL vs 24 μg/dL, p<0.001), and higher in patients who died in hospital (50μg/dL vs 24.3μg/dL, p<0.001). The area under the ROC curve using cortisol to detect any component of MAPE—ETI or ICU admission or in-hospital all-cause mortality—was 0.76 (95% CI, 0.65-0.84). A cortisol value of 31.4μg/dL had sensitivity of 70.8% and specificity of 79.4% for predicting MAPE. Patients in the MAPE group had higher serum cortisol levels than those without any MAPE. Cortisol may be used as a marker to predict MAPE in nontraumatic acutely dyspneic adult patients on ED admission.